Curadoria em arquivos históricos: a “coleção pompeana” do Museu Nacional através da documentação - Vidal, Mariana Silva (2024)
The research investigated the process of formation of the "Coleção Pompeana" of the Museu Nacional da Quinta da Boa Vista through documents belonging to different archival collections. The set from the Real Museo Borbonico, in Naples, is known to have arrived in Brazil through the intermediary of Empress Teresa Cristina; however, the records show us that the collection is the result of multiple efforts, including that of Manuel de Araújo Porto-Alegre, when he was director of Academia Imperial de Belas Artes (AIBA) and of the fourth section of the Museu Nacional. These documents, previously unknown, introduce new agents, indicate origins, circulation and transit of objects, thus allowing us to create a more comprehensive narrative. The arrival of these pieces is linked to the reforms of educational and scientific-cultural institutions initiated in 1854 and coordinated by Couto Ferraz, minister of the Empire. It is therefore revealed as yet another artifice of the Imperial State in the construction of a so-called "civilized" nation. At the end of the 19th century, the collection was expanded and became known as the “Coleção Teresa Cristina” (or “Coleção Mediterrânea”), and came to contain more than seven hundred pieces relating to the Etruscan, Greek and Roman civilizations. However, its composition was reduced to 30% after the fire that struck the Museu Nacional in September 2018. In this sense, the documentation not only helps us to retrace the history of the formation of the collection, but also preserves it to some extent. That is why, at the same time, a database was created with the relevant documents, in order to enable studies on other aspects of the collection. After all, although a small part of what was once the Coleção Teresa Cristina remains, the potential of this collection was not extinguished in the fire